1992
DOI: 10.1126/science.1604322
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB Subunit Regulation in Nontransformed CD4 + T Lymphocytes

Abstract: Regulation of interleukin-2 (IL-2) gene expression by the p50 and p65 subunits of the DNA binding protein NF-kappa B was studied in nontransformed CD4+ T lymphocyte clones. A homodimeric complex of the NF-kappa B p50 subunit was found in resting T cells. The amount of p50-p50 complex decreased after full antigenic stimulation, whereas the amount of the NF-kappa B p50-p65 heterodimer was increased. Increased expression of the IL-2 gene and activity of the IL-2 kappa B DNA binding site correlated with a decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
225
0
1

Year Published

1995
1995
2003
2003

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 314 publications
(239 citation statements)
references
References 51 publications
13
225
0
1
Order By: Relevance
“…In some experimental systems p50/p50 homodimers activated transcription from promoters with speci®c kB sites (Collart et al, 1990;Fujita et al, 1992Fujita et al, , 1993Kretzschmar et al, 1992;Schouten et al, 1995;Ten et al, 1992). In other experimental systems these homodimers were unable to activate gene transcription (Beg et al, 1992;Franzoso et al, 1992;Kang et al, 1992;Plaksin et al, 1993;Schmitz and Baeuerle, 1991). It seems that p50/p50 displays high a nity binding for many distinct kB motifs but provides a strong transcriptional activation only when adopting a speci®c conformation induced by certain kB motifs but not others (Fujita et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…In some experimental systems p50/p50 homodimers activated transcription from promoters with speci®c kB sites (Collart et al, 1990;Fujita et al, 1992Fujita et al, , 1993Kretzschmar et al, 1992;Schouten et al, 1995;Ten et al, 1992). In other experimental systems these homodimers were unable to activate gene transcription (Beg et al, 1992;Franzoso et al, 1992;Kang et al, 1992;Plaksin et al, 1993;Schmitz and Baeuerle, 1991). It seems that p50/p50 displays high a nity binding for many distinct kB motifs but provides a strong transcriptional activation only when adopting a speci®c conformation induced by certain kB motifs but not others (Fujita et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it is particularly interesting that LPS-activated cells expressed a higher level of p50 homodimers relative to heterodimers compared to that of anti-CD40-activated cells. It has been shown that excess of p50 homodimers can reduce activity on some promoters, presumably by replacing binding of p65 or c-Rel-containing heterodimers, which have higher transactivating potential [57,58]. On the other hand, it is possible that the difference in the level of GL ␥1 transcripts induced by LPS and anti-CD40 is independent of NF-B.…”
Section: Discussionmentioning
confidence: 99%
“…Polyclonal rabbit antip50 antibodies were prepared against bacterially produced and affinity purified recombinant mouse p50 as described in Ref. 29, anti-p65 and anti-c-Rel antibodies were from Santa Cruz Biotechnologies.…”
Section: Methodsmentioning
confidence: 99%